PSEUDOMONAS AERUGINOSA lasR MUTANTS ARE ASSOCIATED WITH CYSTIC FIBROSIS LUNG DISEASE PROGRESSION - Hoffman, Lucas R. (2008)
BACKGROUND: Pseudomonas aeruginosa with mutations in the transcriptional regulator LasR chronically infect the airways of people with cystic fibrosis (CF), yet the prevalence and clinical implications of lasR mutant infection are unknown. METHODS: In an exploratory study, we screened 166 P. aeruginosa isolates from 58 CF patients for LasR inactivation and mucoidy, and compared clinical characteristics among source patients. RESULTS: lasR mutation prevalence was comparable to that of mucoidy, the best-described CF-adapted phenotype, but affected patients were on average approximately 2 years younger. In a regression analysis, lung function decline with age was worse among patients with lasR mutant infection than in those without, similar to the effect of mucoidy. CONCLUSIONS: Culture positivity for lasR mutant P. aeruginosa may serve as a marker of early CF adaptive change of prognostic significance. Furthermore, as LasR inactivation alters susceptibility to antibiotics, infection with lasR mutant P. aeruginosa may impact response to therapy.